Efforts To Improve Students' Creativity in Indonesian Language Subjects Using A Project-Based Learning Model in Grade V of State Elementary School 98 Jambi - Andri Rustandi; Bella Chairun Nupus; Abdul Wahid (Journal of Contemporary Islamic Primary Education, 2025)
The purpose of this study was to improve students' creativity through a project-based learning model in grade V of SD Negeri 98 Jambi. This study is a Classroom Action Research (CAR). Where each cycle includes planning, implementation, observation, and reflection carried out in 2 cycles. The subjects and place of research were grade V students of SD Negeri 98 Jambi with a total of 30 students. Data in the study were obtained from observations. Analysis of actions was descriptively qualitative and quantitative. The results of this study indicate that the application of project-based learning models can improve the creativity of fifth-grade students of SD Negeri 98 Jambi. The increase in presentation in each cycle is: cycle I the percentage obtained was 74.6%. In cycle II the percentage increased to 85.3%. The conclusion obtained from the results of this study is that the use of project-based learning models or Project Based Learning (PjBL) can improve the creativity of fifth-grade students of SD Negeri 98 Jambi.